Evaluation of Control Link Impacts on the IRS Assisted Communication System with Hardware-in-the-Loop Simulation - Zeng, Xianshi; Bühlmeyer, Jonas; Weigel, Robert; Irnstorfer, Florian (2024 15th German Microwave Conference (GeMiC), 2024)
With the development of Intelligent Reflecting Surface (IRS) technology, the network performance of the control channel has an increasing impact on IRS systems. This paper presents a hardware-in-the-loop (HiL) simulation methodology for the IRS controller using real network devices. We demonstrate the behaviour of a control channel connected to the simulated IRS-based communication platform. This provides test results that correlate with wired and wireless network connection. In addition, previous work has investigated the mobile user tracking (UT) scheme and proposed methods to achieve a higher signal-to-noise ratio (SNR) in the downlink case, which will provide a theoretical upper bound. Our experimental results are analysed and compared with previous simulation methods. The results show that the proposed HiL simulation methodology can validate the functionality of the UT scheme and emphasise the importance of considering the impact of the non-ideal control link on the IRS system.<br